Experimental rationale and clinical use of radiowave energy, anti-adhesion drugs, placenta cryoextract, range of physiotherapy measures and assisted reproductive technology in the restoration of reproductive function of patients who underwent operative in - Kozub, M. M. (Journal of Education, Health and Sport, 2020)
The aim: to increase the effectiveness of reproductive health restoration in women with progressive tubal pregnancy and develop new approaches to improving methods of restoring reproductive function in patients using endoscopy, anti-adhesive drugs, placental cryoextract, physiotherapy and ART. To substantiate the use of radio wave energy, anti-adhesive drugs, placental cryoextract, an experiment was performed on 196 mature female Wistar rats and 90 BALB / s mice. An analysis of clinical observations of 518 women. The control group included 60 healthy women, 458 patients with tubal pregnancy were divided into 2nd (152 patients), 3rd (154 patients) and 4th (152 patients) clinical groups in which different methods of treatment and rehabilitation of reproductive function were used. It was proved that the use in the 2 clinical group patients PEO with CMC, streptodornase with streptokinase reduced the occurrence of adhesion at 1.6 times, use in patients 3 of the clinical group PEO with CMC, streptodornase with streptokinase and placenta cryoextract led to decrease occurrence of adhesions 2.2 times (p <0.05), use in the 4th clinical group patients sodium hyaluronate, streptodornase with streptokinase and placenta cryoextract helped to reduce the occurence of adhesions by 2.6 times (p < 0.05) compared with the detected intraoperativly adhesion process. The inclusion of ART methods in the treatment of patients who did not become pregnant contributed to the onset of uterine pregnancy in 64.9 - 75.7% of the patients under examination.